Implementasi Smart Cow Farming Technology untuk Monitoring Pertumbuhan Sapi dan Peningkatan Skala Usaha pada Kelompok Peternak Sapi DiBa Farm Kabupaten Lampung Selatan - Pasaribu, A Ferico Octaviansyah; Saputra, Febrian Eko; Wati, Novi Eka; Darwis, Dedi (Universitas Teknokrat Indonesia, 2024)
The DiBa Farm Livestock Group faces several urgent issues that need to be addressed not all cows can achieve the minimum weight gain target of 1.5 kg per day. Monitoring of cow growth productivity is done manually; (3) the calculation of the cost of goods sold is also still done manually. The partner's marketing of livestock products is limited to regular customers within the South Lampung area only. Based on these prioritized issues, the proposed solutions and methods are implementing a wheelbarrow tool with a digital scale for transporting cow feed using IoT technology. Implementing a cow growth monitoring application using RFID. Implementing a website-based application to automatically determine the Cost of Goods Sold for cows. Implementing a digital marketing application for cow sales that can be accessed via a website. Providing training and assistance related to digital marketing strategies. Based on the evaluation results, it was found that the implementation of Smart Cow Farming Technology 100% improved the partners' knowledge of its usage. The average cow growth increased monthly, from 45 kg to 50 kg. Additionally, there was a 25% increase in profits due to the implementation of the cost of goods sold calculation application and the online cow sales application. The evaluation results from the digital marketing training activities also showed that 85% of the partners' knowledge and understanding improved in terms of using digital marketing.